A enfermagem enquanto possibilidade profissional para as mulheres no Brasil na primeira metade do século XX: as trajetórias de Edith Magalhães Fraenkel e Laís Moura Netto dos Reys - Cousseau, Nicoli Malinverno (Universidade do Vale do Rio dos Sinos, 2021)
The main objective of this final course paper focuses on the research and analysis of nursing as a professional possibility for women in Brazil in the first half of the 20th century. In addition, it also seeks to discuss the process of development of modern nursing in Brazil, from the 1920s onwards, with emphasis on Anna Nery School of Nursing (EEAN) (Rio de Janeiro) and to analyze the trajectories of brazilian nurses Edith Magalhães Fraenkel and Laís Moura Netto dos Reys, outstanding characters in the field of nursing in the country in the first half of the 20th century. This study is qualitative research with a socio-historical approach and, for its development, were used sources such as the documentation produced by the Rockefeller Foundation (RF), as the Fellowship Cards of the aforementioned nurses, as well as pertinent bibliographies, such as articles, biographies, books, dissertations, and theses. The process of feminization of nursing began at the beginning of the 20th century and, since its inception, the belief that care, kindness, and abnegation were inherent aspects of the female figure accompanied its development. The understanding that women had their characteristics for domestic work and family care were the supporting pillars for nursing, for a long time, to be conceived as an extension of such feminine obligations. Despite the stigmas of the profession, it is undeniable that nursing meant autonomy and the possibility of women entering the labor market, given that the area presented itself as an occupation of respect, a symbol of devotion and maintenance of society's well-being. From the historiographical perspective, it will be possible to offer contributions to the development of studies focused on both the History of Nursing and nurses, from the dialogue with gender studies, boosting the advancement of research, as well as enriching debates, questions, and reflections within the historiographical field.
Keywords: História da enfermagem; Feminização; Primeira metade do século XX; Edith Magalhães Fraenkel; Laís Moura Netto dos Reys; History of nursing; Feminization; First half of the 20th century